A common variant near BDNF is associated with dietary calcium intake in adolescents - Dušátková, Lenka; Zamrazilová, Hana; Aldhoon-Hainerová, Irena; Sedláčková, Barbora; Včelák, Josef; Hlavatý, Petr; Bendlová, Běla; Kunešová, Marie; Hainer, Vojtěch (Nutrition research, 2015)
Specific targets for most obesity candidate genes discovered by genomewide association studies remain unknown. Such genes are often highly expressed in the hypothalamus, indicating their role in energy homeostasis. We aimed to evaluate the associations of selected gene variants with adiposity and dietary traits. Anthropometric parameters, fat mass, dietary intake (total energy, fat, protein, carbohydrate, fiber, and calcium) and 10 gene variants (in/near TMEM18, SH2B1, KCTD15, PCSK1, BDNF, SEC16B, MC4R and FTO) were analyzed in 1953 Czech individuals aged 10.0 to 18.0 years (1035 nonoverweight and 918 overweight: body mass index [BMI] ≥90th percentile). Obesity risk alleles of TMEM18 rs7561317, SEC16B rs10913469, and FTO rs9939609 were related to increased body weight and BMI (P < .005). The FTO variant also showed a significant positive association with waist circumference and fat mass (P < .001). Overweight adolescents had a lower total energy intake (P < .001) but a higher percentage of fat (P = .009) and protein intake (P < .001) than the nonoverweight subjects. There was also a lower calcium intake in the overweight group (P < .001). An association with at least one component of dietary intake was found in 3 of 10 studied gene variants. The MC4R rs17782313 was associated negatively with protein (P = .012) and positively associated with fiber (P = .032) intakes. The obesity risk alleles of BDNF rs925946 and FTO rs9939609 were related to a lower calcium intake (P = .001 and .037). The effects of FTO and MC4R variants, however, disappeared after corrections for multiple testing. Our results suggest that the common BDNF variant may influence dietary calcium intake independent of BMI.
Keywords: Genotype; Female; Overweight; dítě; energetický příjem; Receptor, Melanocortin, Type 4; ženské pohlaví; jednonukleotidový polymorfismus; Calcium, Dietary; Adolescent; Obesity; stravovací zvyklosti; lidé; Energy Intake; Polymorphism, Single Nucleotide; genotyp; vápník dietní; tělesná hmotnost; obezita; Male; Feeding Behavior; Czech Republic; nadváha; index tělesné hmotnosti; Brain-Derived Neurotrophic Factor; alely; Body Weight; Česká republika; Alleles; mozkový neurotrofický faktor; Child; mužské pohlaví; receptor melanokortinový typ 4; Body Mass Index; mladiství; Humans